The foundations of the metaphysics of the doctrine of law in Kant - Menin Junior , Romeu Felix (Revista Coleta Científica, 2017)
The theme of this article is: The foundation of the metaphysics of the doctrine of law in Kant. The following problem was investigated: Is it considered that the philosopher’s role has fallen into disuse, as a will can be free, while at the same time being subject to the ethical and moral conditions of the norm? The following hypothesis was considered: This freedom defended by the philosopher may depend on the possibility for its existence to be possible and may be free if it depends on the determination of conformity with the laws. The general objective of this work is to analyze how the philosopher in the face of contradictions will develop rational solutions for submission to the ethical and moral conditions of the norm. The Specific Objectives of this work are: to analyze the supreme principle of morality; moral action and the concepts of reason and highlight the metaphysical character of both morals and law, addressed by Kantian works. This work is important in an individual and collective perspective, because in the introduction of the study of Law Philosophy appears as a foundation and over the years within the legal and academic life, the norm goes more and more against custom, entering the individual compass. This is a qualitative theoretical research lasting six months. Upon concluding the study on the issues that underlie the metaphysics of customs, Kant no longer mentions anthropological dualism, man as nature and reason, in sustaining the idea that part of the rational, intelligible world, the human will will be free and overlap about all the influences of the sensitive nature. For it can strengthen the metaphysical character of Kantian morals.